2003
DOI: 10.1074/jbc.m307964200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Induction by Bradykinin in Human Pulmonary Artery Smooth Muscle Cells Is Mediated by the Cyclic AMP Response Element through a Novel Autocrine Loop Involving Endogenous Prostaglandin E2, E-prostanoid 2 (EP2), and EP4 Receptors

Abstract: Bradykinin (BK) is an important mediator in several inflammatory and vascular diseases that acts in part via induction of cyclooxygenase-2 (COX-2). The mechanisms involved in BK-mediated COX-2 induction are unclear.Here we characterized the transcriptional mechanisms involved in human pulmonary artery smooth muscle cells. BK stimulated the activity of a transiently transfected 966-bp (؊917 to ؉ 49) COX-2 promoter luciferase reporter construct. There was no reduction in BK-induced luciferase activity in cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 31 publications
3
49
1
Order By: Relevance
“…Consistent with observations in other cell types (38,43), stimulation of B2 receptors significantly enhanced COX-2 mRNA in MG-63 cells and in mouse calvarial bones. In addition, this study was the first to show that a BK B1 receptor agonist significantly enhanced COX-2 mRNA in both the human osteoblastic cell line MG-63 and in mouse calvariae.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with observations in other cell types (38,43), stimulation of B2 receptors significantly enhanced COX-2 mRNA in MG-63 cells and in mouse calvarial bones. In addition, this study was the first to show that a BK B1 receptor agonist significantly enhanced COX-2 mRNA in both the human osteoblastic cell line MG-63 and in mouse calvariae.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to this, we find a positive feed-forward loop involving the prostanoid PGE 2 after mechanical disruption of endothelial cell monolayers that aids recovery of monolayer integrity. PGE 2 stimulates endothelial cell cyclooxygenase-2 expression at low nanomolar levels, as recently found for cyclooxygenase 2 accumulation in pulmonary artery smooth muscle cells after bradykinin stimulation (28). PGE 2 accumulated to levels (ϳ6 nM) sufficient to stimulate cyclooxygenase-2 expression after wounding confluent monolayers even in the absence of an exogenous source of arachidonate.…”
Section: Figmentioning
confidence: 75%
“…In foreskin fibroblasts, COX-2 induction by IL-1␤ used the C/EBP-binding domain (45). In airway smooth muscle cells, BK-induced COX-2 expression was mediated by CCAAT/enhancer protein but not by NF-B or C/EBP, whereas NF-B was involved in IL-1␤-induced COX-2 expression (46). The results of this study showed that NF-B activation contributed to BK-induced COX-2 induction in A549 cells, and that the inhibitors of the NF-B-dependent signaling pathway, including PDTC and TPCK, inhibited BK-induced COX-2 expression.…”
Section: Discussionmentioning
confidence: 95%